Presidential referral of a bill to the Sejm for reconsideration vs discontinuation of parliamentary proceedings - Piotrowski, Ryszard (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
If the President, prior to signing a bill, has not referred it to the Constitutional Tribunal, he may return the said bill, with a memorandum of explanation attached, to the Sejm for reconsideration. This kind of presidential veto has the effect of suspending the bill, in line with the constitutional model of the president-parliament relationship, as arising from the principle of separation of powers. In practice, it may happen that a bill has been sent for reconsideration shortly before the end of the Sejm’s term and the law makers had no time to respond to the presidential referral. In such case, in accordance with the principle of discontinuation, the veto proceedings are closed, and the president’s suspending veto turns into an absolute veto. The constitutional interpretation in support of such veto transformation fails to allow for the consequences of the separation-of-powers principle, which rules out vesting the head of state with non-appealable and irrevocable decision-making powers in respect of a bill. The interpretative ambiguity over application of the discontinuation principle to the presidential veto should be resolved in such a way as to respect the basic constitutional values and principles that underpin system-of-governance rationality.